Belief polarization and Covid-19 - Gene Ambrocio; Iftekhar Hasan (Bank of Finland, 2022)
We document a remarkable increase in economic belief polarization - disagreement - regarding the future state of the economy across Europe during the Covid-19 pandemic. We find evidence suggesting that belief polarization may have impeded the implementation of pandemic response measures such as social distancing and teleworking as well as policies providing economic support. We find an association between belief polarization on the one hand and trust in the press, fake news, political polarization, and possibly also inequality on the other. These results indicate that belief polarization, by hindering the implementation of crisis response policies, may be one channel which could amplify the negative effects of large or unusual crises.
urn:nbn:fi:bof-202209201384
Keywords: E23; E66; E71; I12; 330; Polarization; consumer survey; Covid-19